Cyclosporin population pharmacokinetics in pediatric refractory nephrotic syndrome based on real-world studies: Effects of body weight and spirolactone administration - Wang, Dongdong (Exp Ther Med, 2019)
Different models of population pharmacokinetics (PPK) of cyclosporin have been established in various populations. However, the cyclosporin PPK model in patients with pediatric refractory nephrotic syndrome (PRNS) has yet to be constructed. The present study aimed to establish the cyclosporin PPK model in PRNS, and to identify factors that may account for any variability. Chinese patients with PRNS treated with cyclosporin between June 2014 and June 2018 at the Children's Hospital of Fudan University (Shanghai, China) were retrospectively analyzed. The impact of demographic features, laboratory parameters and concomitant medications was evaluated. A total of 18 PRNS patients from real-world studies were analyzed by non-linear mixed-effects modeling. A one-compartment model with first-order absorption and elimination was selected as the appropriate model in PRNS. Body weight (WT) and spirolactone intake were included as significant covariates for the apparent oral clearance (CL/F), and the WT was revealed to significantly influence the apparent volume of distribution (V/F). The final covariate models were as follows: CL/F=80.7 × (WT/70)(0.75) × (1-0.265×θ(spirolactone)), and V/F=2,030 × (WT/70), where θ(spirolactone) is the coefficient of spirolactone. The inter-individual variability in CL/F and V/F was 44.6 and 53.1%, respectively. In conclusion, in the present study, a cyclosporin PPK model for patients with PRNS was successfully constructed, and the presence of a clinically significant interaction between spirolactone and cyclosporin in PRNS patients was determined based on real-world studies, indicating that concomitant medication with spirolactone was able to reduce cyclosporin clearance in the patients with PRNS.